Corporate governance in sustainability indexes: a Spanish case study - Andreu-Pinillos, Alberto (2020)
In recent years, corporate governance and corporate social responsibility have come closer in academic research, and especially on sustainability indexes. In fact, the most significant indexes handle the matter of corporate governance along with other environmental and social criteria. The purpose of this study is to find out if all the variables included in the corporate governance dimension on the above mentioned indicators are equally relevant and material for both corporate social responsability and corporate governance. To carry out the study, a sample of academics and professionals from Spanish universities and businesses sector was taken. We defend the plausible hypothesis that not all items included within corporate governance dimension on sustainability indexes are homogeneous and interchangeable and, therefore, equally relevant. As a result, the measurements provided by these indexes may not be truly representative.